Non-state forms of conflict resolution: opportunities for improving criminal justice a case study of community courts in Mozambique - Lorizzo, Concetta (Department of Public Law, 2023)
The Mozambican criminal justice system faces two main challenges, namely lack of access to justice for all and deplorable prison conditions. Judicial courts are distant and expensive; legal terminology is incomprehensible to the majority of people; and prisons are overcrowded. Mozambicans continue to rely on different normative systems, other than state justice, to resolve their disputes. Recognised mainly as informal, these non-state mechanisms have always been considered as closer, cheaper and faster than judicial courts. However, the literature on legal pluralism and the state has historically ignored the role that they play in criminal justice. Given this background, the thesis examines the limitations of legal pluralism and how the past shaped and continues to shape the particular relationship of the state with community courts in relation to criminal justice. The study makes use of materials derived from exploratory work in the Mozambican capital city of Maputo, including focus group discussions, individual interviews, access to case files, and various other empirical observations. The thesis analyses the functioning of community courts. The discourses and practices on criminal justice of these courts are most usually seen as situated within Eurocentric dominant political discourses about the nature of access to justice and punishment. Through a postcolonial analysis, however, the thesis aims at identifying community courts as forms of local knowledge; it explores the legal and practical obstacles and opportunities that community courts provide to improve access to criminal justice for petty crimes and ultimately their impact on the condition of prisons. The thesis shows that the revision of the community courts' law presents an opportunity to broaden the competence of the courts to include criminal cases punishable with imprisonment up to three years. Because of this, petty crimes would go through the state criminal justice system and more cases would be resolved at the community level. Community courts are trusted by the people and make use of a form of restorative justice. They reach decisions through mediation; assess the socioeconomic causes of a case; involve families and communities when needed; and apply alternatives to imprisonment. A shift of the state's mainstream attitude to community courts in relation to criminal justice is now needed – a move away from Eurocentric discourse and towards the recognition, in practice, of local knowledge.